2020
DOI: 10.1038/s41598-020-57651-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of Soil Seed Banks in Ex-closures for Restoration of Degraded Lands in the Central Rift Valley of Ethiopia

Abstract: Soil seed banks (SSB) can be important components in the process of rehabilitating degraded lands. Thus, this study was aimed to evaluate the role of SSB to the restoration of degraded lands in six, fifteen and twenty-five year’s ex-closures and adjacent degraded open grazing land (DOGL). Totally, 160 samples of SSB from four soil layers (litter, 0–3 cm, 3–6 cm & 6–9 cm), four sites and ten in a composite of 5 (15 × 15 cm) were collected and tested for seed viability through seed extraction and seedling em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Study on the SSB is important, since it is one of the most important functional parts of any plant community and can be a significant component in the process of rehabilitating degraded lands (Mohammed & Denboba, 2020). Bakker (1989) identified SSBs as non‐mature seeds buried in soil that can replace existing vegetation if it becomes degraded.…”
Section: Introductionmentioning
confidence: 99%
“…Study on the SSB is important, since it is one of the most important functional parts of any plant community and can be a significant component in the process of rehabilitating degraded lands (Mohammed & Denboba, 2020). Bakker (1989) identified SSBs as non‐mature seeds buried in soil that can replace existing vegetation if it becomes degraded.…”
Section: Introductionmentioning
confidence: 99%
“…Despite widespread reports of the impacts of restoration on plant community structure and soil properties, studies on soil seed banks in degraded and restored grasslands are lacking and, when examined, are generally limited to a single sampling period (Engst et al 2017). It was reported that management regimes, above-ground vegetation, and soil properties affected the soil seed bank composition and diversity in a saline-alkaline grasslands (Mohammed and Denboba 2020). Deferred grazing from spring to autumn and rotational grazing increased the soil seed bank of perennial and annual grasses (Nie et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the above-ground vegetation, soil seed bank (SSB) is the main constituent of each ecosystem because it is a potentially major propagule source that can have a significant input to vegetation composition (Li et al, 2011;Rusvai & Cz obel, 2021) and strongly influences the plant communities resilience (Yang et al, 2021). SSB determines essential ecological processes by maintaining biodiversity (Lee & Marrs, 2021) and recovery of damaged plant communities (Mohammed & Denboba, 2020). Nevertheless, the spatial and temporal variation of SSBs, their densities and composition changes when accompanied by disturbances are not fully understood in ecosystems (Erfanzadah et al, 2022), particularly in some sensitive habitats such as alpine grasslands.…”
Section: Introductionmentioning
confidence: 99%